Paracetamol modulates biofilm formation in Staphylococcus aureus clonal complex 8 strains - Sultan, Andi R.; Lattwein, Kirby R.; Lemmens-den Toom, Nicole A.; Snijders, Susan V.; Kooiman, Klazina; Verbon, Annelies; van Wamel, Willem J. B. (Scientific reports, 2021)
Staphylococcus aureus biofilms are a major problem in modern healthcare due to their resistance to immune system defenses and antibiotic treatments. Certain analgesic agents are able to modulate S. aureus biofilm formation, but currently no evidence exists if paracetamol, often combined with antibiotic treatment, also has this effect. Therefore, we aimed to investigate if paracetamol can modulate S. aureus biofilm formation. Considering that certain regulatory pathways for biofilm formation and virulence factor production by S. aureus are linked, we further investigated the effect of paracetamol on immune modulator production. The in vitro biofilm mass of 21 S. aureus strains from 9 genetic backgrounds was measured in the presence of paracetamol. Based on biofilm mass quantity, we further investigated paracetamol-induced biofilm alterations using a bacterial viability assay combined with N-Acetylglucosamine staining. Isothermal microcalorimetry was used to monitor the effect of paracetamol on bacterial metabolism within biofilms and green fluorescent protein (GFP) promoter fusion technology for transcription of staphylococcal complement inhibitor (SCIN). Clinically relevant concentrations of paracetamol enhanced biofilm formation particularly among strains belonging to clonal complex 8 (CC8), but had minimal effect on S. aureus planktonic growth. The increase of biofilm mass can be attributed to the marked increase of N-Acetylglucosamine containing components of the extracellular matrix, presumably polysaccharide intercellular adhesion. Biofilms of RN6390A (CC8) showed a significant increase in the immune modulator SCIN transcription during co-incubation with low concentrations of paracetamol. Our data indicate that paracetamol can enhance biofilm formation. The clinical relevance needs to be further investigated.